Association between the composite dietary antioxidant index and the prevalence and recurrence of kidney stones: results of a nationwide survey - Zhu, Huan; Chen, Yinmei; Feng, Yue; Chen, Hui (Frontiers in Nutrition, 2024)
Abstract Aim: This study aims to evaluate the relationship between the Composite Dietary Antioxidant Index (CDAI) and the prevalence and recurrence of kidney stones. Methods: Data from the National Health and Nutrition Examination Survey (NHANES) collected between 2007 and 2014 were used in this cross-sectional analysis. The CDAI was derived by standardizing the intake of dietary antioxidants from 24-hour dietary recalls. The study assessed the prevalence and recurrence of kidney stones based on questionnaire responses. The association between the CDAI and both the prevalence and recurrence of kidney stones was investigated using multivariable logistic regression. Subgroup analyses and interaction tests further evaluated the robustness of this relationship. Results: The study included 20,743 participants, and the reported incidence and recurrence rates of kidney stones were 9.09% and 2.90%, respectively. After stratifying the CDAI into tertiles, an inverse trend was observed in both kidney stones' prevalence and recurrence probabilities with increasing CDAI levels. Adjusting for confounding factors, individuals in the top tertile had a 23% lower prevalence of kidney stones (OR = 0.77, 95% CI: 0.66, 0.90, p=0.0011) and a 39% lower recurrence rate (OR = 0.61, 95% CI: 0.47, 0.80, p=0.0003) than those in the bottom tertile. In addition, interaction tests showed that age, gender, body mass index, hypertension, and diabetes did not significantly affect the relationship between CDAI levels and kidney stone prevalence and recurrence rates. Conclusion: Our study suggests that increased levels of CDAI are associated with reduced incidence and recurrence rates of kidney stones. Therefore, increasing the intake of dietary antioxidants may be an effective strategy for preventing kidney stones and their recurrence.